2016
DOI: 10.1021/acscatal.6b00750
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for High Selectivity in the Hydrodeoxygenation of 5-Hydroxymethylfurfural over PtCo Nanocrystals

Abstract: Carbon-supported, Pt and PtCo nanocrystals (NCs) with controlled size and composition were synthesized and examined for hydrodeoxygenation (HDO) of 5-hydroxymethylfurfural (HMF). Experiments in a continuous flow reactor with 1-propanol solvent, at 120 to 160 °C and 33 bar H2, demonstrated that reaction is sequential on both Pt and PtCo alloys, with 2,5-dimethylfuran (DMF) formed as an intermediate product. However, the reaction of DMF is greatly suppressed on the alloys, such that a Pt3Co2 catalyst achieved DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
136
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 138 publications
(149 citation statements)
references
References 58 publications
10
136
0
Order By: Relevance
“…In another example involving the reaction of HMF, Wang et al [10] reported that catalysts based on Pt-Co nanoparticles, encapsulated in hollow carbon spheres, could give DMF yields as high as 98%. We have recently confirmed this result on carbon-supported Pt-Co nanocrystals (NCs), without the carbon hollow-spheres, and further showed that the bimetallic catalysts exhibit much better stability than the monometallic catalysts [11]. The high selectivity of the Pt-Co catalysts resulted from the fact that DMF is unreactive over the bimetallic catalyst.…”
Section: Introductionmentioning
confidence: 65%
See 4 more Smart Citations
“…In another example involving the reaction of HMF, Wang et al [10] reported that catalysts based on Pt-Co nanoparticles, encapsulated in hollow carbon spheres, could give DMF yields as high as 98%. We have recently confirmed this result on carbon-supported Pt-Co nanocrystals (NCs), without the carbon hollow-spheres, and further showed that the bimetallic catalysts exhibit much better stability than the monometallic catalysts [11]. The high selectivity of the Pt-Co catalysts resulted from the fact that DMF is unreactive over the bimetallic catalyst.…”
Section: Introductionmentioning
confidence: 65%
“…It is not likely that the higher yields are due to the increase in temperature. In addition to the fact that previous work indicated that selectivities are not very different between 100 and 200 °C [11,22], one would expect the reaction of DMF to over-hydrogenated products to increase with temperature. The maximum in the yield as a function of space time in Figure 6 is clearly less steep than that found for Pt 6 Ni/C and PtNi/C catalysts.…”
Section: Hydrodeoxygenation Of Hmf In a Continuous Flow Reactormentioning
confidence: 98%
See 3 more Smart Citations